Dry needling on tendons and myofascial trigger points in post-traumatic stiffness of elbow: a case report - Shanmugam, Sukumar; Shetty, Kavitha; Mathias, Lawrence; Santhumayor, Rebecca (International Journal of Research in Medical Sciences, 2017)
A 42 years old female presented with the complaints of pain and stiffness of right elbow with limited elbow extension, since 8 months, due to fracture of head of the radius. She was receiving conventional physical therapy treatment for pain relief and functional improvement since eight months. The limitation in Elbow extension caused difficulty in carrying household works. Later the patient was treated with dry needling to myofascial trigger points in brachioradiallis, common flexor, and extensor muscles of elbow and upper trapezius of shoulder, dry needling for tendons were added for further muscle relaxation. The interventions were carried out for three sessions, alternatively for one week. Pain (VAS score from 8/10 to 1/10), elbow extension range of motion (from 120º-35º to 120º-05º) and the patient’s upper limb functions (Quick DASH score from 63.36 to 13.63) were improved after one week of intervention. This case report results suggest that overall neuro-musculoskeletal function was improved due to dry needle induced myofascial trigger points deactivation and further muscle relaxation caused by tendon needling. This case report may helpful in formulating further treatment tool for better and faster recovery from pain and joint dysfunction in post immobilization pain and stiffness of elbow and other joints.